Hunter demography, trends and correlates of hunting participation in Sweden - Lindberg, Erik (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2010)
The concerning issue of declining number of hunters in North America is also apparent in Europe and Sweden. When the bulk of research found on human dimensions and hunting participation has almost exclusively been done in the United States, this report seeks to add to the needed knowledge on a national level focusing on the causes of hunter declines related to social factors within Sweden. Using hunter data reaching from commune, county to National level, this report describes the correlation between a number of variables and the hunting participation in Sweden. The typical Swedish hunter lives in an area with low population density, the person usually has higher education, the living situation is stable with no recent moving and there is relatively good access to forest land. Persons with weaker connection to the Swedish culture such as foreign citizens, people with foreign background and people born outside “the Nordic countries” are less likely to start hunt or participate in hunting. A strong relationship was found between the favorite game, moose (Alces alces), and the amount of hunters participating in the hunting. Merged with the quantity of roe deer (Capreolus capreolus) and wild boar (Sus scrofa) it gives a reliable estimation of the amount of hunters likely to participate in a given year.